2016
DOI: 10.1002/bies.201600129
|View full text |Cite
|
Sign up to set email alerts
|

A SUMO and ubiquitin code coordinates protein traffic at replication factories

Abstract: Post-translational modifications regulate each step of DNA replication to ensure the faithful transmission of genetic information. In this context, we recently showed that deubiquitination of SUMO2/3 and SUMOylated proteins by USP7 helps to create a SUMO-rich and ubiquitin-low environment around replisomes that is necessary to maintain the activity of replication forks and for new origin firing. We propose that a two-flag system mediates the collective concentration of factors at sites of DNA replication, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…USP7 was identified as a DUB that removes ubiquitin from SUMO. Intriguingly, upon USP7 inhibition, SUMOylated proteins are collectively displaced from the replisome, which fully abrogates DNA replication, both by limiting fork progression and the firing of new origins (Lecona and Fernandez-Capetillo, 2016;.…”
Section: Sumo Chains At Replisomesmentioning
confidence: 99%
See 1 more Smart Citation
“…USP7 was identified as a DUB that removes ubiquitin from SUMO. Intriguingly, upon USP7 inhibition, SUMOylated proteins are collectively displaced from the replisome, which fully abrogates DNA replication, both by limiting fork progression and the firing of new origins (Lecona and Fernandez-Capetillo, 2016;.…”
Section: Sumo Chains At Replisomesmentioning
confidence: 99%
“…Ulp2, as well as SENP6 and SENP7 preferentially act on SUMO chains thereby countering the StUbL pathway. While SENP6 and SENP7 antagonize the StUbL pathway by limiting SUMO chain formation, two deubiquitylating enzymes, namely USP7 and USP11, possibly counter RNF4 signaling by catalyzing the removal of ubiquitin from SUMO2 polymers (Hendriks et al, 2015;Lecona and Fernandez-Capetillo, 2016;.…”
mentioning
confidence: 99%
“…71 Hence, SUMO-dependent deubiquitylation might be an effective means of generating and maintaining a Ubiquitin-poor environment at sites of DNA replication as recently suggested. 70,72 Further, USP7 disassembles Rad18-dependent poly-ubiquitin chains and compromises UVinduced PCNA mono-ubiquitylation in the DNA damage tolerance pathway. [73][74][75] As detailed below, USP7 operates with UVSSA during TC-NER.…”
Section: Regulation Of Poly-ubiquitylation By Parylation and Deubiquimentioning
confidence: 99%
“…Although the exact functions of replisome SUMOylation remain to be elucidated, a recent report showed that the SUMOylation of the catalytic subunit of DNA polymerase ε is important for DNA replication in yeast [64,65]. In addition to the SUMOylation of specific factors, we have proposed that the collective SUMOylation of the replication machinery supports DNA replication by creating an environment that facilitates interactions among replication factors [84], analogous to the SUMO-based group modification model proposed by Stefan Jentsch for DNA repair [85]. Within this model, we previously showed that USP7 is a SUMO-dependent deubiquitinase that maintains low levels of ubiquitination in the replisome, and whose action is necessary to sustain DNA replication [24].…”
Section: Sumo and Ubiquitin In Dna Replicationmentioning
confidence: 99%
“…The ubiquitination of the CMG could also be limited by specific DUBs, and we have previously identified USP7 as a SUMO-specific deubiquitinase that maintains a SUMO-rich/ubiquitin-poor environment at the DNA replication forks [24,81]. In this sense, SUMO could act as a signal to drive the ubiquitination of replication factors upon DNA replication termination or compete for ubiquitination to prevent the untimely modification of these proteins [84]. In yeast, the MCM2-7 complex has been shown to be SUMOylated in G1, and MCM7 SUMOylation persists during the S phase [66].…”
Section: Replisome Disassembly At the End Of Dna Replicationmentioning
confidence: 99%